2015
DOI: 10.1073/pnas.1417273112
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Atrial natriuretic peptide prevents cancer metastasis through vascular endothelial cells

Abstract: SignificancePostoperative cancer recurrence is a major problem following curative cancer surgery. Perioperative systemic inflammation induces the adhesion of circulating tumor cells released from the primary tumor to the vascular endothelium of distant organs, which is the first step in hematogenous metastasis. We have previously reported that administration of atrial natriuretic peptide (ANP) during the perioperative period reduces inflammatory response and has a prophylactic effect on postoperative cardiopul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 36 publications
2
94
0
Order By: Relevance
“…A recent study reported that atrial natriuretic peptide (ANP), a polypeptide hormone that induces cGMP up-regulation through the natriuretic peptide receptor, drastically suppressed the recurrence of lung cancer after curative surgery (45). In this clinical study, the 2-year relapse-free survival rate in the propensity score-matched analysis was also significantly greater in ANP-treated patients than in control patients (91 versus 67%, p ϭ 0.0013).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A recent study reported that atrial natriuretic peptide (ANP), a polypeptide hormone that induces cGMP up-regulation through the natriuretic peptide receptor, drastically suppressed the recurrence of lung cancer after curative surgery (45). In this clinical study, the 2-year relapse-free survival rate in the propensity score-matched analysis was also significantly greater in ANP-treated patients than in control patients (91 versus 67%, p ϭ 0.0013).…”
Section: Discussionmentioning
confidence: 71%
“…Unwilling TLR4 signaling-induced low grade inflammation are widely involved in several types of disease including obesityinduced inflammation (13), atherogenesis (47), Alzheimer's disease (50), tumor metastasis (45), and the adverse effect of opioids (37). However, the effective countermeasures for suppressing TLR4 signaling is not established.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) To expand the adaptation of ANP for cancer therapy, however, the detailed mechanism of action of ANP should be further investigated. In this study, we explored the effects of ANP on HUVEC cells at different time points, and found that the molecular mechanism underlying the impacts of ANP on endothelial cells may change over time.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profile data: To explore the molecular mechanisms of ANP in vascular endothelial cells, the gene expression data GSE56976 6 for HUVEC was downloaded from NCBI GEO (Gene Expression Omnibus; http://www. ncbi.nlm.nih.gov/geo) as TXT files.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation